EFFICIENCY OF THE PRODUCTION SCALE OF POLISH DAIRY COMPANIES BASED ON DATA ENVELOPMENT ANALYSIS - Baran, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2013)
This article presents evaluation of efficiency of the production scale of Polish milk processing companies in 1999-2010 performed basing on non-parametric methods. The non-parametric approach stemmed from linear programming method known as the Data Envelopment Analysis (DEA) method. The study involving a sample of 743 objects revealed increasing returns to scale observable in the Polish dairy sector. Further concentration of the dairy sector in Poland should lead to the better results of dairies. This analysis confirmed earlier conclusions of relevant literature.